2019
DOI: 10.1093/jbcr/irz063
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into Possible Association of Oxandrolone and Heterotopic Ossification Following Burn Injury

Abstract: Oxandrolone, a testosterone analog, is used to counteract the catabolic effects of burn injury. Recent animal studies suggest a possible hormonal association with heterotopic ossification (HO) development postburn. This work examines oxandrolone administration and HO development by exploring historical clinical data bridging the introduction of oxandrolone into clinical practice. Additionally, we examine associations between oxandrolone administration and HO in a standardized mouse model of burn/trauma-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Testosterone might play a role in the gender difference of burn-induced HO. Thorpe et al [62] found that acutely burned patients who received a testosterone analog treatment presented a higher incidence of elbow HO than patients without testosterone analog treatment. In a mouse model following burn/tenotomy, testosterone analog treatment conferred a trend of developing a larger volume of HO lesions [62].…”
Section: Other Factors Associated With the Mechanisms Of Burn-induced Homentioning
confidence: 99%
“…Testosterone might play a role in the gender difference of burn-induced HO. Thorpe et al [62] found that acutely burned patients who received a testosterone analog treatment presented a higher incidence of elbow HO than patients without testosterone analog treatment. In a mouse model following burn/tenotomy, testosterone analog treatment conferred a trend of developing a larger volume of HO lesions [62].…”
Section: Other Factors Associated With the Mechanisms Of Burn-induced Homentioning
confidence: 99%
“…Burn wounds. A dorsal burn injury with concurrent Achilles tenotomy was induced on 6-week-old male C57BL/6 mice as previously described [13]. The mice were housed individually under standard conditions with free access to drinking water and food.…”
Section: Murine Wound Modelsmentioning
confidence: 99%